Pengaruh Model Jigsaw Terhadap Hasil Belajar IPS di Sekolah Dasar - Paradila, Paradila; Arwin, Arwin; Alwi, Elma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to effect of Jigsaw model on student learning outcomes in Social Science Class V at SDN 52 Kuranji kota Padang, in the odd semester of the academic year 2018/2019. This research is a quantitative research with experimental type and quasy experimental research design. Population of this study amounted to 240 people, sampling data is taken by purposive sampling, with a sample of 40 people. Based on the research that has been done, the average posttest of experiment class 78,2 and control class 70,55 with difference 7,65 number, next research obtained t count> t table, 4,388 > 1,6859 with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of Jigsaw model of student learning outcomes in Social Science Class V SDN 52 Kuranji kota Padang.Keyword : Jigsaw model, student learning outcomes IPS